Spatial and temporal evolution of the eco-efficiency of cultivated land use in the region around Beijing–Tianjin based on the Super-EBM model - Li, Xiaoqing; Zhao, Li; Chang, Xinhan; Yu, Jie; Song, Xinming; Zhang, Lizhu (Frontiers in Ecology and Evolution, 2023)
The eco-efficiency of cultivated land use (ECLU) is an important indicator for ecological civilization construction in China. Exploring the spatiotemporal dynamic evolution of the ECLU is helpful for the sustainable use of arable land, ensuring food security and ecological security. However, previous studies have mostly focused on the use of a slacks-based measure (SBM) model for ECLU measurement, ignoring the more accurate epsilon-based measure (EBM) model. Therefore, in this study, first, we explored the conceptual framework of the ECLU, and then, based on 2005-2020 panel data covering the counties in the region around Beijing and Tianjin, we investigated the spatial and temporal evolution of the ECLU by using the Super-EBM model, kernel density estimation method, and spatial Markov chain model. The results show the following: (1) From 2005 to 2020, the ECLU in the region around Beijing and Tianjin displayed an increasing state, but the average value was only 0.55. (2) The temporal evolution of the ECLU has gradually polarized, and the internal gap has widened, but it tends to stabilize. (3) The ECLU in the region around Beijing and Tianjin was more inclined to remain the same, and there was a "club convergence" phenomenon, which was meaningfully affected by the background of neighboring areas. In light of local conditions, the government should reasonably formulate a path to optimize the ECLU, strengthen the linkage with surrounding cities, and bring into play the positive spillover effect.